Catalog of Endophytic Insects Associated with Rosinweeds (Silphium L., Heliantheae, Asteraceae) in North America - Louis F. Nastasi; Cecil N. Smith; John F. Tooker; Andrew R. Deans (Psyche: A Journal of Entomology)
Endophytic insects, including gall insects and leaf miners, are prominent in both natural and agricultural plant communities. We catalog the endophytic insect fauna in North America that are known to associate with rosinweeds (Silphium L., Heliantheae, Asteraceae). We provide details on host plant species, brief descriptions of insect associations, and known distributions of their association with Silphium species. We report associations with rosinweeds for 41 insect species from 18 families across four insect orders and detail the host plant tissue where these insects occur. The complex community we describe suggests that a further study of rosinweed endophytic insects could be useful to understanding evolution of host-plant preferences and Silphium species boundaries.